Sentido de vida para pessoas idosas no processo de escolarização na educação de jovens e adultos - Fonseca, Mônica da Mota (2023)
The presence of elderly individuals in today’s society is a reality that prompts us to reflect upon the meaning of life for the elderly in the context EJA (Youth and Adult Education). This compels us to face numerous theoretical and practical challenges in order to consider the existential aspect of elderly life, aiming for an excellent quality of life. The significance of this theme motivated us to investigate how returning to education affects their quality of life, bringing about, changing and/or providing assistance to the meaning of life for each student. Therefore, the main objective of this research was to analyze the perceptions of elderly students enrolled in EJA regarding their educational process and its contribution to the construction of their sense of life. The specific objectives were: (i) to identify the meaning of life for EJA elderly students; (ii) to investigate the implications of the educational process in the lives of these elderly students; and (iii) to analyze, based on the perceptions of elderly EJA students, how the school has contributed to mitigating problems related to the aging process and to constructing a meaning of life. The study utilized a qualitative approach with a phenomenological focus. It was conducted in two schools in João Pessoa-PB, involving students aged 60 years or older. The research employed semi-structured interviews, and the analysis was grounded in the phenomenology of Husserl (1996), the phenomenology of perception by Merleau-Ponty (1999), and Viktor Frankl's (2008) existentialist theory on the meaning of life. The results revealed, in the voices of the participant subjects, subcategories related to happiness, well-being, fulfillment, joy, the will to continue living, and the dream of learning to read and write. Non-verbal perceptions were also expressed through body language, reactions and postures intertwined with the emotion of reminiscing about the past, all connected to their sense of meaning of life. Thus, the meaning of life experienced by elderly students in EJA was transformative, as they redefined their ways of living. In conclusion, this research underscores the need for education to update its methodologies, stimulating and encouraging elderly individuals to engage in meaningful schooling that leads to happiness and a meaning of life.